2015
DOI: 10.1371/journal.pntd.0003914
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Recombinant Canine Distemper Virus Expressing Leishmania Antigen against Leishmania Challenge in Dogs

Abstract: Canine distemper virus (CDV) vaccination confers long-term protection against CDV reinfection. To investigate the utility of CDV as a polyvalent vaccine vector for Leishmania, we generated recombinant CDVs, based on an avirulent Yanaka strain, that expressed Leishmania antigens: LACK, TSA, or LmSTI1 (rCDV–LACK, rCDV–TSA, and rCDV–LmSTI1, respectively). Dogs immunized with rCDV-LACK were protected against challenge with lethal doses of virulent CDV, in the same way as the parental Yanaka strain. To evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Morbilliviruses stably incorporate additional genes in their genome, and immunization with such a bi- or multivalent virus elicits humoral and cellular immune responses against the added proteins [73]. Strong immunogenicity of the first such MeV vaccine carrying a chikungunya virus antigen has been seen in a clinical phase I trial [74], and the efficacy of a leishmania antigen-expressing CDV has been demonstrated in dogs [75], illustrating the potential of this platform.…”
Section: Vaccine and Drug Developmentmentioning
confidence: 99%
“…Morbilliviruses stably incorporate additional genes in their genome, and immunization with such a bi- or multivalent virus elicits humoral and cellular immune responses against the added proteins [73]. Strong immunogenicity of the first such MeV vaccine carrying a chikungunya virus antigen has been seen in a clinical phase I trial [74], and the efficacy of a leishmania antigen-expressing CDV has been demonstrated in dogs [75], illustrating the potential of this platform.…”
Section: Vaccine and Drug Developmentmentioning
confidence: 99%
“…The chimeric virus was shown to be safe for both mice and dogs and resulted in the production of long-lasting neutralizing antibodies against both CDV and rabies, and even protected mice from a lethal dose of rabies, demonstrating potential for the production of multivalent vaccines against both pathogens [31,35]. A recombinant avirulent CDV strain expressing Leishmania antigens (leishmania homolog of receptors for activated C-kinase (LACK), thiol-specific antioxidant (TSA), or protein antigen LmSTI1 (LmSTI1), was also reported suitable for use as a polyvalent vaccine vector for Leishmania, providing protection against both CDV and major infections of Leishmania in dogs [69]. In addition, the generation of recombinant CDV expressing interleukin (IL)-18 or IL-7 also showed that they could be potentially used as molecular immunoadjuvants and agents for anticancer therapies in vivo [70,71].…”
Section: Recombinants As Safe and Efficient Candidate Multivalentmentioning
confidence: 99%
“…Importantly, a virus-based vector must not only be satisfactorily attenuated but must also maintain sufficient replication efficiency in cultured cells for enabling its production in amounts that allow it to be immunogenic in the host. In comparison with other RNA virus vectors, CDV as a replication-competent vector appears to be clearly superior, as it can deliver foreign antigens in vivo with high efficacy for enabling the systemic spread and preferential infection of professional antigen presenting cells (APCs) and lymphoid and epithelial tissues; these vectors also show significant expression efficiency for foreign antigens as candidate multivalent vaccines [31,35,39,69].…”
Section: Recombinants As Safe and Efficient Candidate Multivalentmentioning
confidence: 99%
“…In brief, MBR membranes have relatively small pore sizes (0.03-0.40 µm), resulting in the physical exclusion of a wide variety of microorganisms (Ottoson et al, 2006;Simmons et al, 2011). Although most viruses are smaller than the membrane pore sizes presently used in many MBR systems, recent studies have reported high removal values for viruses Simmons et al, 2011;Hai et al, 2014;Chaudhry et al, 2015;Miura et al, 2015;Purnell et al, 2015;. Consequentely, there is still some disagreement as to the most important mechanisms for virus removal in MBR systems, but it is thought to be primarily influenced by the development of a biofilm on the membrane, and by virus adsorption to this biomass Shang et al, 2009;Hirani et al, 2014;van den Akker et al, 2014).…”
Section: Membrane Bioreactor (Mbr) Systemsmentioning
confidence: 99%
“…Other workers have monitored fecal indicators alongside pathogenic viruses in MBR directly using qPCR methodologies, which are based on the detection of nucleic acids, rather than complete, infectious particles (virions). In a range of studies, MBR treatment systems have recorded removal rates of between 3.9 and 5.5 log 10 units for adenovirus (Adv), 1.3 and 4.1 log 10 units for sapovirus (SaV), 0.2 and 5.7 log 10 units for norovirus (NoV GII), 0.3 and 3.6 log 10 units for enterovirus, and 3.3 and 6.8 log 10 units for calcivirus (CaV) (Chaudhry et al, 2015;Miura et al, 2015;Ottoson et al, 2006;Sima et al, 2011;Simmons et al, 2011). Whilst qPCR allows for the detection of unculturable pathogens, such as NoV, the detection of nucleic acids from damaged particles in treated product, may lead to over-estimates of the potential risk to human health from reuse water.…”
Section: Membrane Bioreactor (Mbr) Systemsmentioning
confidence: 99%